Durability performance of high volume fly ash roller compacted concrete pavement containing crumb rubber and nano silica. Issue 12 (14th October 2020) - Adamu, Musa; Mohammed, Bashar S.; Shafiq, Nasir; Liew, Mohd Shahir
ABSTRACT: This study investigated the effect of a hybrid of crumb rubber and nano silica on the durability performance (Porosity and Permeability) and skid resistance of high volume fly ash (HVFA) roller compacted concrete (RCC) pavement. The HVFA RCC pavement was developed with 50% cement by volume replaced using fly ash. Crumb rubber was used to partially replace fine aggregate at varying percentages, i.e. 0%, 10%, 20%, and 30% by volume replacement. Nano silica was added by weight of cementitious materials at variations of 0%, 1%, 2%, and 3%. The Vebe consistency, water absorption, and mercury intrusion porosimetry were used to measure the consistency, permeability, and porosity of the HVFA RCC pavement, respectively. The skid resistance was measured in terms of the British Pendulum Number (BPN) using the British Pendulum Tester (BPT). The result findings showed that the HVFA increased the consistency, rate of water absorption, and porosity of the RCC pavement. Furthermore, the consistency, water absorption, and porosity of the HVFA RCC pavement increased with an increase in the partial replacement of the fine aggregate with crumb rubber. On the contrary, the addition of nano silica decreased the consistency, rate of water absorption, and porosity of the HVFA RCC pavement. This was due to the larger surface area, finer size, and physiochemical reaction of the nano silica which resulted in pore structure refinement in the hardened matrix of the HVFA RCC pavement by filling the voids within the interconnected pores thereby breaking the interconnectivity and reducing its diameter. The results of the skid resistance showed that incorporation of 10% crumb rubber as the replacement to fine aggregate and addition of up to 2% nano silica by weight of cementitious materials increased the skid resistance of the HVFA RCC pavement.